Charter Schools 1995 - Thomas Mauhs-Pugh (Arizona State University, 1995)
This report is the result of a group project undertaken by Tom Mauhs-Pugh's class in Policy and Politics in American Education at Dartmouth College during March-May of 1995. Specific attribution of authorship will be given in the text for relevant sections.